2021
DOI: 10.1002/smll.202102051
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Resistance Two‐Stage Electrostatically Assisted Air Filtration by Polydopamine Coated PET Coarse Filter

Abstract: Airborne particulate matters (PM) pose serious health threats to the population, and efficient filtration is needed for indoor and vehicular environments. However, there is an intrinsic conflict between filtration efficiency, air resistance, and service life. In this study, a two‐stage electrostatically assisted air (EAA) filtration device is designed and the efficiency‐air resistance‐filter life envelope is significantly improved by a thin coating of polydopamine (PDA) on the polyethylene terephthalate (PET) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…Using an electric field to clean air have been a known topic in the past, yet has been mostly focused on removing particles such as dust, soot, etc. [20] , [21] . Most of such systems use fibrous filtration although, there is an intrinsic conflict between filtration efficiency, low air resistance, and long service life.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…Using an electric field to clean air have been a known topic in the past, yet has been mostly focused on removing particles such as dust, soot, etc. [20] , [21] . Most of such systems use fibrous filtration although, there is an intrinsic conflict between filtration efficiency, low air resistance, and long service life.…”
Section: Hardware In Contextmentioning
confidence: 99%
“…Numerous studies have revealed that one of the most effective ways to dilute VOCs is by ventilation [12][13][14][15]. In addition, air purification is also important for indoor pollution control [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…People spend most of their time indoors, and pollutants in indoor air are an important cause of human diseases [1][2][3][4]. As one of the main indoor pollutants, formaldehyde has the characteristics of wide sources, significant harm, and a long release period [5,6].…”
Section: Introductionmentioning
confidence: 99%